History of Coin Minting in Yerevan - Teymur Kuliyev (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The purpose of the article is to study the coinage in Yerevan, which is one of the ancient cities of the Caucasus, located on the most important trade routes. The study of the history of the Yerevan Mint is important for the study of topical socio-economic and political issues of the history of the Caucasus. Methods and materials. Based on the comparative method, the article examines the coinage in Erivan using written and numismatic sources. Along with the descriptions of coins given by R.S. Pul, A.K. Markov, R. Fasmer, E.A. Pakhomov, M.A. Seyfeddini, A.M. Rajabli, E.A. Sinitsyna, and A.V. Hakobyan, information taken from medieval written historical sources containing important data on Yerevan, such as the works of Arakel Davrizhetsi, Zakaria Akulisi, Kirakos Gandzaketsi, Parsadan Gorgijanizde, Evliya Chelyabi, and Iskender bek Munshi Turkman, is also used. Analysis and results. Having arisen during the period of weakening of the Hulaguid state, the Yerevan Mint began periodically minting coins under the Safavid dynasty and under subsequent rulers from the Afsharid dynasty, Zand dynasty, and Qajar dynasty. Tаnka was fought in Yerevan until the mid-90s of the 16th century. The catalogs describe the tankas minted at the Yerevan Mint on behalf of Tahmasp I and Ismail II. As a result of the monetary reform of Abbas the Great in 1595, abbasi weighing 7.8 grams began to be minted at the Yerevan mint. The location of the Erivan Khanate on favorable trade routes contributed to the activation of the mint of the Erivan Khanate. The coins found in the Caucasian coin hoards, minted at the Yerevan mint, testify to the developed trade relations of Yerevan with the countries of the East. Until 1828, the monetary circulation and coinage of the Erivan/Yerevan Khanate were integral parts of the currency and coinage of Qajar Iran.